KUL-KUL CONNECTION: PARTISIPASI ANAK-ANAK SEKOLAH DALAM PROGRAM PEDULI LINGKUNGAN DI GREEN SCHOOL BALI - Mia Dian Triska, Ni Luh Gde; Kebayantini, Ni Luh Nyoman; Sastri Mahadewi, Ni Made Anggita (JURNAL ILMIAH SOSIOLOGI (SOROT), 2020)
This journal aims to analyze the participation of localschoolchildrenin environmentalprogramsat the Green School Bali which is bridged by the Kul-Kul Connection which is a community integration in the Green School Bali. This study uses a qualitative approach with descriptive and explanative types. The author uses three propositions from six propositions of social exchangetheory George Caspar Homans, namely success propositions, stimulus propositionsandvalue propositions. Environmentalprogramsinthe Kul-Kul Connection include trash for class, activism, rice cycle course, and grebek. Local school children who are members of the Kul-Kul Connection show participation and care for the environment in participating in environmental programs. The impact from the participation of school children on environmental care, the impact of caring for the environment at home, the impact of caring for the environment in schools, the impact of caring for the environment in society. Keywords: Kul-Kul Connection, participation, school children, environmental program, Green School Bali